The Role of Gender in Factors Associated With Addiction Treatment Satisfaction Among Long-Term Opioid Users. Issue 5 (September 2015) - Marchand, Kirsten; Palis, Heather; Peng, Defen; Fikowski, Jill; Harrison, Scott; Spittal, Patricia; Schechter, Martin T.; Oviedo-Joekes, Eugenia
Abstract : Objectives: To identify factors associated with Opioid Agonist Treatment (OAT) satisfaction and to determine whether these relationships are gender specific. Methods: This study was based on data collected in a cross-sectional study among long-term opioid-dependent individuals (n = 160; 46.3% women). Participants completed the Client Satisfaction Questionnaire in reference to OAT episodes. Sociodemographic, illicit substance use, health, and addiction treatment history data were collected. Multivariable linear regression was used to determine the relationship between these variables and treatment satisfaction. To explore the potential role of gender in these identified relationships stratified multivariable models were tested. Additional open-ended questions regarding positive and negative perceptions of treatment were collected, and a thematic analysis was conducted. Results: In the multivariable linear regression model, participants who were older, of Aboriginal ancestry, and currently receiving OAT had higher OAT satisfaction scores, whereas participants who had methadone dose preferences of 30 mg or less had lower OAT satisfaction. In stratified analyses among women, the relationship between preferred methadone dose and current OAT remained significantly associated with satisfaction. Open-ended positive and negative perceptions complemented and provided further valuable data to interpret these identified relationships. Conclusions: To our knowledge, this is the first study to explore the potential role of gender in factors associated with OAT satisfaction. These findings provide valuable information to health care providers working in OAT settings regarding how to address women and men's OAT needs and improve treatment satisfaction.